Rapamycin‐Induced Hypoxia Inducible Factor 2A Is Essential for Chondrogenic Differentiation of Amniotic Fluid Stem Cells. (29th March 2016) - Preitschopf, Andrea; Schörghofer, David; Kinslechner, Katharina; Schütz, Birgit; Zwickl, Hannes; Rosner, Margit; Joó, József Gabor; Nehrer, Stefan; Hengstschläger, Markus; Mikula, Mario
Abstract : This study investigated the effects of mammalian target of rapamycin complex 1 (mTORC1) modulation on the expression of SOX9 and its downstream targets during chondrogenic differentiation of amniotic fluid stem (AFS) cells. mTORC1 inhibition led to upregulation of chondrogenic markers during AFS cell differentiation and during redifferentiation of in vitro‐expanded human chondrocytes. Abstract : Amniotic fluid stem (AFS) cells represent a major source of donor cells for cartilage repair. Recently, it became clear that mammalian target of rapamycin (mTOR) inhibition has beneficial effects on cartilage homeostasis, but the effect of mTOR on chondrogenic differentiation is still elusive. Therefore, the objectives of this study were to investigate the effects of mammalian target of rapamycin complex 1 (mTORC1) modulation on the expression of SOX9 and on its downstream targets during chondrogenic differentiation of AFS cells. We performed three‐dimensional pellet culturing of AFS cells and of in vitro‐expanded, human‐derived chondrocytes in the presence of chondrogenic factors. Inhibition of mTORC1 by rapamycin or by small interfering RNA‐mediated targeting of raptor (gene name, RPTOR ) led to increased AKT activation, upregulation of hypoxia inducible factor (HIF) 2A, and an increase in SOX9, COL2A1, and ACAN abundance. Here we show that HIF2A expression is essential for chondrogenic differentiation and that AKT activity regulates HIF2A amounts. Importantly, engraftment of AFS cells in cell pellets composed of human chondrocytes revealed an advantage of raptor knockdown cells compared with control cells in their ability to express SOX9. Our results demonstrate that mTORC1 inhibition leads to AKT activation and an increase in HIF2A expression. Therefore, we suggest that mTORC1 inhibition is a powerful tool for enhancing chondrogenic differentiation of AFS cells and also of in vitro‐expanded adult chondrocytes before transplantation. Significance: Repair of cartilage defects is still an unresolved issue in regenerative medicine. Results of this study showed that inhibition of the mammalian target of rapamycin complex 1 (mTORC1) pathway, by rapamycin or by small interfering RNA‐mediated targeting of raptor (gene name, RPTOR ), enhanced amniotic fluid stem cell differentiation toward a chondrocytic phenotype and increased their engrafting efficiency into cartilaginous structures. Moreover, freshly isolated and in vitro passaged human chondrocytes also showed redifferentiation upon mTORC1 inhibition during culturing. Therefore, this study revealed that rapamycin could enable a more efficient clinical use of cell‐based therapy approaches to treat articular cartilage defects.